Sequence-specific dimerization of a transmembrane helix in amphipol A8-35. - Michael Stangl; Sebastian Unger; Sandro Keller; Dirk Schneider (PLoS ONE, 2014)
As traditional detergents might destabilize or even denature membrane proteins, amphiphilic polymers have moved into the focus of membrane-protein research in recent years. Thus far, Amphipols are the best studied amphiphilic copolymers, having a hydrophilic backbone with short hydrophobic chains. However, since stabilizing as well as destabilizing effects of the Amphipol belt on the structure of membrane proteins have been described, we systematically analyze the impact of the most commonly used Amphipol A8-35 on the structure and stability of a well-defined transmembrane protein model, the glycophorin A transmembrane helix dimer. Amphipols are not able to directly extract proteins from their native membranes, and detergents are typically replaced by Amphipols only after protein extraction from membranes. As Amphipols form mixed micelles with detergents, a better understanding of Amphipol-detergent interactions is required. Therefore, we analyze the interaction of A8-35 with the anionic detergent sodium dodecyl sulfate and describe the impact of the mixed-micelle-like system on the stability of a transmembrane helix dimer. As A8-35 may highly stabilize and thereby rigidify a transmembrane protein structure, modest destabilization by controlled addition of detergents and formation of mixed micellar systems might be helpful to preserve the function of a membrane protein in Amphipol environments.